2001
DOI: 10.1007/s004840000081
|View full text |Cite
|
Sign up to set email alerts
|

The role of temperature in the onset of the Olea europaea L. pollen season in southwestern Spain

Abstract: Temperature is one of the main factors affecting the flowering of Mediterranean trees. In the case of Olea europaea L., a low-temperature period prior to bud development is essential to interrupt dormancy. After that, and once a base temperature is reached, the plant accumulates heat until flowering starts. Different methods of obtaining the best-forecast model for the onset date of the O. europaea pollen season, using temperature as the predictive parameter, are proposed in this paper. An 18-year pollen and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
65
4
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(77 citation statements)
references
References 13 publications
(21 reference statements)
6
65
4
2
Order By: Relevance
“…In our study, average and minimum temperatures observed from January through March were among the most important independent variables to predict the total APC and the onset date of the Olea MPS. Similar results were also observed for Cordoba (Galán et al 2001;Vázquez et al 2003) although only with the average mean temperatures of January and March which were found to be the best variables for forecasting total APC. During this period the flower buds start their development leading to inflorescence growth and anther formation.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…In our study, average and minimum temperatures observed from January through March were among the most important independent variables to predict the total APC and the onset date of the Olea MPS. Similar results were also observed for Cordoba (Galán et al 2001;Vázquez et al 2003) although only with the average mean temperatures of January and March which were found to be the best variables for forecasting total APC. During this period the flower buds start their development leading to inflorescence growth and anther formation.…”
Section: Discussionsupporting
confidence: 81%
“…The values of R 2 and R 2 adj obtained in our study are higher than the ones obtained for Cartagena when using the regression models developed in Spain, (Moreno-Grau et al 2000) but very similar to those obtained in Có rdoba (Galán et al 2001;Vázquez et al 2003). The non-existence of a forecasting model for the total APC in the BRA and the lower R 2 obtained for the combination of all regions could be due to the influence of meteorological parameters.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Pollen data can be used as a phenological indicator of flowering, and many phenological studies using pollen data have been conducted in order to determine the chilling and heat requirements for flowering in various species and geographical areas (Garcia-Mozo et al, 2000;Jato et al, 2000;Fornaciari, et al, 2000a;Gala´n et al, 2001;Laaidi, 2001). Meteorological data are usually supplied by local weather stations to enable calculation of thermic phenological indexes; accurate determination of the start of the Gala´n et al (1995) and Lejoly-Gabriel and Leuschner (1983) in 2002 and according to the criteria of Gala´n et al (1995) and Spieksma et al (1995) Feher and Ja`rai-Komlo´di (1997) and Lejoly-Gabriel and Leuschner (1983) in 2002 and according to the criteria of Feher and Ja`rai-Komlo´di (1997) and Spieksma et al (1995Spieksma et al ( ) in 2003 pollen season according to local flowering is therefore essential.…”
Section: Discussionmentioning
confidence: 99%